AUDIT MANAJEMEN ATAS FUNGSI SUMBER DAYA MANUSIA PADA PABRIK ASPAL GRESIK PT. PERTAMINA (PERSERO) UPms V - Hudha, Mohamad Syamsul; Siswanto, Moch. Hadi (GEMA EKONOMI, 2012)
Basically the human resources function in companies should be implemented, because the function is ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã¢â‚¬Å“Service DepartmentÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€šÃ‚Â (the pernbantu / services) is tasked to help resolve any staffing issues faced by every business leader and manager status as human resources staff personnel assistant leader of the company. Audit management is one type of evaluation that rnemungkinkan the management company know the extent of implementation of the corporate plan can be accomplished, as well as the establishment of control that can be understood by management karyawan.Audit in fact still very rarely done, because they have become a tradition, or as well as the absence of regulations necessitated a management audit.This study aims to determine the human resources function is executed in accordance with the procedures (laws and regulations) that have been defined and determine the level of effectiveness and efficiency of human resource functions for each activity. The study used here is the kind of case study research that is descriptive, because the business is limited to reveal a problem or situation or event as it is, so its the fact (fact finding). The results of this study emphasized the idea of objective truth about the state of the object under study, namely how human resource management applied to the human resources function.Conclusion The results of research on the management audit of human resource functions at Asphalt Plant PT Gresik. Pertamina (Persero) UPMS V, is: The human resources in carrying out or attempting to run the operations in accordance with established policy, the welfare of employees is in accordance with the policies and capabilities, not breaking the law in the management of labor, in doing dekrutmen already have some consideration, the reasons and the rights of employees to be acquired, and the last of the audit is done, it can be said that the human resources function in PT Gresik Asphalt Plant. Pertamina (Persero) UPMS V has been carrying out activities quite effectively in achieving the targets and the efficient use of the cost to employees. This is proven by the acceptance and placement of workers in accordance with the field and the expertise of each